THE ROLE OF THE FAMILY IN INCREASING ENVIRONMENTAL CONCERN IN EARLY CHILDHOOD - Sihotang, Ijah Mulyani (Proceeding International Seminar of Islamic Studies, 2024)
The purpose of this article is to describe the role of the family in increasing environmental awareness in children from an early age. This problem is motivated by the human obligation to protect the environment so that the environment is balanced, the low level of public awareness in protecting the environment, Islam requires humans to protect the environment according to the recommendations in the Al-Qur'an Ar-rum verse 41 which means: There has been real damage on land and in the sea caused by human hands, Allah wants them to feel some of it. (as a result of) their actions, so that they return (to the right path).” This research is descriptive research in the form of a literature study. By reviewing several literature and scientific articles related to the role of the family in increasing environmental awareness in children from an early age. Based on the results of the analysis, the family plays an important role in increasing awareness of the environment from an early age.